2019
DOI: 10.1515/cllt-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

Pluralized non-count nouns across Englishes: A corpus-linguistic approach to variety types

Abstract: This corpus-based study of pluralized non-count nouns (informations, advices, etc.) uses collocation-derived measures (determiners vs. bare noun and mass quantifiers) to extract potential candidates of non-count nouns in a bottom-up approach from the British National Corpus (BNC), allowing the detection of grammatical categories from distributional features. We then use this token list to retrieve data on pluralization of non-counts from nine annotated components of the International Corpus of English (ICE). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Lieberman et al (2007), based on a corpus study of inflectional changes in irregular verbs, predict that many irregular verbs, such as break, choose, and draw, are likely to become regularised. Similarly, Schneider et al (2020) found that non-standard pluralisation of uncountable nouns is regularly observed among non-native speakers and also occasionally among native speakers of English. In fact, there are some other corpus studies which have discovered variant forms of standard features, such as sentence-initial conjunctions (Liu, 2008), was-indicative in the unreal subjunctive (Phoocharoensil, 2014), and the indicative verb form in the mandative subjunctive (Grund & Walker, 2006).…”
Section: Introductionmentioning
confidence: 75%
“…Lieberman et al (2007), based on a corpus study of inflectional changes in irregular verbs, predict that many irregular verbs, such as break, choose, and draw, are likely to become regularised. Similarly, Schneider et al (2020) found that non-standard pluralisation of uncountable nouns is regularly observed among non-native speakers and also occasionally among native speakers of English. In fact, there are some other corpus studies which have discovered variant forms of standard features, such as sentence-initial conjunctions (Liu, 2008), was-indicative in the unreal subjunctive (Phoocharoensil, 2014), and the indicative verb form in the mandative subjunctive (Grund & Walker, 2006).…”
Section: Introductionmentioning
confidence: 75%
“…It is advisable to supplement evidence from synchronic corpora with historical data since patterns that are identified as instances of nativization in ESL varieties (e.g. the extension of pluralization to non-counts) may also have precursors in earlier stages of English (Hundt 2016b, Schneider et al, 2019. In other words, for the historical study of WEs, researchers not only need stratified diachronic corpora of ESL varieties to fill in the gaps but ideally also diachronic evidence on regional and nonstandard varieties of English to gauge the effect that different input varieties may have had on the development of WEs.…”
Section: Discussionmentioning
confidence: 99%
“…Most corpus-based approaches to syntactic variation choose a single construction to examine and then model variation within that construction alone (Buchstaller, 2008;Grieve, 2012;Schilk and Schaub, 2016;Calle-Martin and Romero-Barranco, 2017;Grafmiller and Szmrecsanyi, 2018;Deshors and Götz, 2020;Schneider et al, 2020;Rautionaho and Hundt, 2022;Xu et al, 2022;Larsson, 2023;Li et al, 2023). While this line of work can reveal small-scale syntactic variation and change, it can never account for grammatical variation.…”
Section: Related Workmentioning
confidence: 99%